2022
DOI: 10.1371/journal.pone.0277969
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the universality of nudging: A cross-cultural comparison of the information effects of reminding people about familial support

Abstract: Nudging is a method for eliciting a desired behavior. One approach to nudging involves information provision. When information presented for this purpose is designed from an evolutionary perspective, it may reveal a deeper level of rationality within human decision-making that might otherwise appear to be irrational. Based on insights from the evolution of altruism, we previously designed a message to remind people of the benefits they have received from the actions of relatives to realize industrialization. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…These trends were similar to our previous studies that investigated the message effects highlighting familial support to moderate risk-averse attitudes on a wide variety of topics [ 33 36 ]. The maximum values for these correlation coefficients were 0.12 [ 34 ], 0.21 [ 35 ], and 0.13 [ 36 ], respectively. The maximum value for our current study was 0.13, which was within the value range from our previous similar studies, and thus is reasonable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These trends were similar to our previous studies that investigated the message effects highlighting familial support to moderate risk-averse attitudes on a wide variety of topics [ 33 36 ]. The maximum values for these correlation coefficients were 0.12 [ 34 ], 0.21 [ 35 ], and 0.13 [ 36 ], respectively. The maximum value for our current study was 0.13, which was within the value range from our previous similar studies, and thus is reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…COVID pr measured how much respondents were preoccupied with COVID-19. These variables were introduced because we found that attitudes to COVID-19 could influence the intervention effects for other topics [ 34 , 35 ]. OWP se was a dummy variable to identify whether respondents have seen OWP before or not, considering that familiarity with the risk source could moderate risk-averse attitudes [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the cost of sending reminders should be considered, especially when developing a real-world intervention policy. Meanwhile, previous study has indicated that nudging effects may vary due to factors like personal traits, cultural distinctions, and social settings 48 . Considering personal factors like age and gender for tailored reminder letters is recommended when developing the intervention.…”
Section: Discussionmentioning
confidence: 99%